Experimental investigations of the interface between steam and water two phase flows - Afrasyab, Khan; Noaman, Ul Haq; Imran Rafiq, Chughtai; Ajmal, Shah; K., Sanaullah (Elsevier Ltd., 2014)
Hydrodynamic instabilities play an important role in the design of those systems operated at high temperature and pressure. The creation and propagation of Kelvin–Helmholtz (KH) instabilities has been experimentally investigated here for the first time in condensable fluids i.e. steam and water. Generally, in case of these condensable fluids the instabilities are so much short lived that it’s very difficult to record them. Here the instabilities occurred in the close vicinity of the steam–water interface, were attributed mainly to the temperature fluctuations of micro scale or less. Supersonic steam was injected inside the subcooled water at inlet pressure varying from 1.5 bar to 3.0 bar by using a specially designed supersonic nozzle, whereas temperature of water inside the vessel was raised from 30 C to 60 C at an increment of 50 each. Kelvin–Helmholtz instabilities in the form of minor as well as amplified transient temperature fluctuations were recorded using a specially designed apparatus that uses LM35 sensors and data acquisition system. This system is capable to record temperatures at a rate of one millisecond and was also capable to record the temperatures anywhere inside the vessel. It was also found out that the instabilities created at the interface propagated towards the axis of the geometry as well as these instabilities were strongly affected by change in tank water temperature and inlet pressure